Study of the influence of the interfacial transition zone on the elastic modulus of concrete using a triphasic model. Issue 9 (2nd May 2016) - Aouissi, F.; Yang, C. C.; Brahma, A.; Bederina, M.
Abstract: Concrete can be considered as a three-phase composite material composed of cement matrix, aggregate particles, and interface transition zone (ITZ). Generally, the ITZ presents particular characteristics that can reduce the properties of concrete and therefore limits its performance. Thus, with such complex structures, this zone is the weakest zone of the composite. The evaluation of the effective behavior of composite using predictive models requires a consideration of this zone. In this context, an approach based on the model of double inclusion and on the Mori–Tanaka theory to predict the elastic modulus of concrete has been used. This approach will be compared with some analytical biphasic model such as Reuss model, Voigt model, the Voigt and Reus combined models, and Hashin and Shtrikman models. Many experimental results are considered in the confrontation. So the developed model predicts very satisfactorily the elastic modulus of the concrete unlike other models in which a discrepancy in the results is demonstrated in the majority of cases.